Sustainable energy for sustainable development: Malaysian perspective on renewable and alternative energy sources - Ansari, Abdul Haseeb (2014)

(untitled)
For achieving the imperatives of sustainable development, sustainable energy is central. In view of this, reliance on fossil fuels for power generation has to be gradually shifted to renewable and alternative energy sources. All states are striving hard to maximize these environmentally friendly energy sources. But developing and least developed countries, due to lack of enough environmentally sound technologies (ESTs) and paucity of financial resources, have not been able to do much. It is for these reasons that their power generation targets in their plans are relatively low and are likely not to be achieved within the stipulated times. In order to divert the money given as subsidy for petrol and diesel towards developmental activities of common interest, they are also gradually withdrawing the subsidy. Malaysia is no exception to this. Being a developing country and keen to boost its economy to achieve the target of being a developed country by 2020, it is striving hard by all means to achieve the target, which is not so attractive but within its reach, set to be achieved by 2020. It is worth mentioning that Malaysia is 25th among the most sustainably developed countries in the world. The paper discusses the Malaysian perspectives on these issues, especially issues pertaining to renewables. The paper concludes that the objective set by the government with respect to these energy sources will certainly be achieved, and which will, in turn, add to the sustainable development strategies of the country and wellbeing of its people, provided it gets enough support from developed countries.